Systemic Lupus Erythematosus Flare Triggered by Mosquito Bite Manifesting as Febrile Targetoid Rash - Joe Khodeir; Hamad El Hajj; Paul Ohanian (Clinical Case Reports)
ABSTRACT Insect bites can trigger disease flare in systemic lupus erythematosus, including atypical targetoid rash. Awareness of such triggers and appropriate preventive measures are crucial for effective SLE management.